Peculiarities of Termination of Employment Relations with an Employer's Representative at the Initiative of the Employer - Haykyants, Armen; Karapetyan, Mane (Bulletin of Yerevan University C: Jurisprudence, 2022)
The topic of the Article is dedicated to the institute of termination ofemployment relations with the employer's representative. The special role of the employer's representative, as a subject of labor law, characterizes the uniqueness of his/herstatus, as a result of which both general and special regulations of the labor legislationare applied in relations with him/her. In this context, it is obvious that unlike other employees of the organization, the employment legal status of the employer's representative is dualistic, since, on the one hand, he/she enters into employment contracts onbehalf of the employer or applies disciplinary measures as an example, and on the otherhand, he/she performs work and receives a salary. Within the scope of this Article, theexperience of foreign countries was studied, doctrinal approaches were referred to, andthe existing RA judicial practice on the issue was presented alongside with the practiceof the Republic of Armenia around the problem. Having completed the work, the authors proposed to legislate also the specifics of termination of employment relationswith an employer's representative, establishing the right of organizations to terminate anemployment contract concluded with an employer's representative without any groundsand at any time.
Keywords: Termination of employment contract; representative of the employer; employer initiative; judicial practice; joint-Stock Company; working status; foreign and international experience